An application of the Pareto method in surveys to diagnose managers' and workers' perception of occupational safety and health on selected Polish construction sites - Obolewicz, Jerzy; Dąbrowski, Andrzej (International journal of occupational safety and ergonomics, 2018)
The construction industry is an important sector of the economy in Poland. According to the National Labour Inspectorate (PIP) data of 2014, the number of victims of fatal accidents in the construction sector amounted to 80 as compared with 187 injured in all other sectors of economy in Poland. This article presents the results of surveys on the impact of construction worker behaviour on the occupational safety and health outcomes. The surveys took into account the point of view of both construction site management (tactical level) and construction workers (operational level). For the analysis of results, the method of numerical taxonomy and Pareto charts was employed, which allowed the authors to identify the areas of occupational safety and health at both an operational and a tactical level, in which improvement actions needed to be proposed for workers employed in micro, small, medium and large construction enterprises.